Establishment of Tree Shrew Animal Model for Kaposi’s Sarcoma-Associated Herpesvirus (HHV-8) Infection - Li, Daoqun; Baloch, Zulqarnain; Zhao, Yang; Bai, Lei; Wang, Xing; Wang, Gang; Zhang, A-Mei; Lan, Ke; Xia, Xueshan (Frontiers in Microbiology, 2021)
Kaposi's sarcoma-associated herpesvirus (KSHV) is the most common cause of Kaposi's sarcoma (KS) and other malignancies in humans. However, the lack of a KSHV-infected small animal model has hampered understanding the mechanisms of KSHV infection, virus replication, pathogenesis, and persistence. This study was designed to explore the susceptibility of tree shrews as a possible KSHV-infected small animal model. A recombinant GFP (latent)/RFP (lytic)-positive rKSHV.219 strain was used to infect primary cells cultured from different tissues of tree shrews as in vitro model and adult tree shrew as in vivo model. KSHV latent nuclear antigen (LANA) and DNA were successfully detected in primary cells of tree shrews. Among them, tree shrew kidney epithelial cells (TSKEC) were the most susceptible cells to KSHV infection compared to other cells. KSHV genomic DNA, mRNA, and KSHV-specific proteins were readily detected in the TSKEC cultured up to 32dpi. Moreover, KSHV DNA and mRNA transcription were also readily detected in the peripheral blood mononuclear cells (PBMCs) and various tissues of tree shrews infected with KSHV. Haematoxylin and eosin (HE) staining showed lymphocyte infiltration, lymphoid tissue focal aggregation, alveolar wall thickening, hepatocyte edema, hepatic necrosis in the spleen, lung, and liver of KSHV infected animals. Additionally, immune-histochemical (IHC) staining showed that LANA or ORF62-positive cells were present in the spleens, lung, liver, and kidney of KSHV infected tree shrews. Here, we have successfully established in vitro and in vivo KSHV latent infection in tree shrews. This small animal model is not only useful for studying the pathogenesis of KSHV in vivo but can also be a useful model to study transmission routes of viral infection and a useful platform to characterize the novel therapeutics against KSHV.